Indonesian Migrant Community Behavior and Awareness in Providing Education Rights for Children - Aththoillah, Muhammad Sabiq; Mahardhani, Ardhana Januar; Cahyono, Hadi; Majid, Ikhwanuddin Abdul (Didaktika Religia, 2024)
Migrant workers frequently encounter a multitude of challenges, including a lack of official documentation such as deeds, family cards, passports, and residence permits. The absence of these documents precludes migrant workers from exercising their rights, including the right to send their children to school and access healthcare. The objective of this research is to analyse the behaviour of Indonesian migrant communities and their awareness of the necessity to provide children with the right to education. The research methodology employed is qualitative, with a descriptive approach. The subjects of this research are the Indonesian migrant community and the manager of Sanggar Bimbing Gombak Utara. The data were collected through a combination of interviews, observation, and document analysis. The data analysis techniques employed included data reduction, data presentation, and conclusion drawing. The results demonstrate that migrant workers demonstrate a high level of responsibility with regard to their children’s education rights. Despite the constraints they face in relation to legal documents, migrant workers adopt a proactive approach in seeking solutions. The government’s initiative through the Sanggar Bimbingan illustrates its commitment to fulfilling the right to education. The research findings indicate that, despite facing economic challenges, migrant workers continue to prioritise their children’s education.